Data science: Building visual understanding - Nugroho, Agung Yuliyanto (Jurnal Teknologi Cerdas, 2024)
Data science is rapidly evolving and plays a vital role in a variety of fields, from business to healthcare. However, the complexity of the data generated often makes it difficult for stakeholders without a technical background to understand. Data visualization is here to bridge this gap, enabling complex information to be translated into more intuitive and understandable graphical representations. Through effective visualization, patterns, trends, and insights hidden in data can be identified more quickly, facilitating better and faster decision-making. This article explores the critical role of visualization in data science, discussing the key techniques used to transform raw data into informative visualizations. It will also discuss how choosing the right visualization can help uncover relationships between variables, facilitate predictive analysis, and support in-depth analytical processes. By integrating visualization into the data science workflow, we can not only accelerate understanding but also improve communication between technical and non-technical teams. Ultimately, visualization is not just a supporting tool, but a core element that helps transform data into valuable insights.